Angiotensin receptor blockers and risk of cancer: cohort study among people receiving antihypertensive drugs in UK General Practice Research Database. (24th April 2012) - Bhaskaran, Krishnan; Douglas, Ian; Evans, Stephen; van Staa, Tjeerd; Smeeth, Liam
Abstract : Objectives To investigate whether there is an association between use of angiotensin receptor blockers and risk of cancer. Design Cohort study of risk of cancer in people treated with angiotensin receptor blockers compared with angiotensin converting enzyme (ACE) inhibitors. Effects were explored with time updated covariates in Cox models adjusted for age, sex, body mass index (BMI), diabetes and metformin/insulin use, hypertension, heart failure, statin use, socioeconomic status, alcohol, smoking, and calendar year. Absolute changes in risk were predicted from a Poisson model incorporating the strongest determinants of risk from the main analysis. Setting UK primary care practices contributing to the General Practice Research Database. Participants 377 649 new users of angiotensin receptor blockers or ACE inhibitors with at least one year of initial treatment. Main outcome measures Adjusted hazard ratios for all cancer and major site specific cancers (breast, lung, colon, prostate) by exposure to angiotensin receptor blockers and by cumulative duration of use. Results Follow-up ended a median of 4.6 years after the start of treatment; 20 203 cancers were observed. There was no evidence of any increase in overall risk of cancer among those ever exposed to angiotensin receptor blockers (adjusted hazard ratio 1.03, 95% confidence interval 0.99 to 1.06, P=0.10). For specific cancers, there was some evidence of an increased risk of breast and prostate cancer (1.11, 1.01 to 1.21, P=0.02; and 1.10, 1.00 to 1.20, P=0.04; respectively), which in absolute terms corresponded to an estimated 0.5 and 1.1 extra cases, respectively, per 1000 person years of follow-up among those with the highest baseline risk. Longer duration of treatment did not seem to be associated with higher risk (P>0.15 in each case). There was a decreased risk of lung cancer (0.84, 0.75 to 0.94), but no effect on colon cancer (1.02, 0.91 to 1.16). Conclusions Use of angiotensin receptor blockers was not associated with an increased risk of cancer overall. Observed increased risks for breast and prostate cancer were small in absolute terms, and the lack of association with duration of treatment meant that non-causal explanations could not be excluded.